Implementasi Pembelajaran PAI dan Budi dalam Kurikulum Merdeka di SMKK Negeri 1 Kutasari Purbalingga - Aulia Sabrina, Wilda; Hidayat, Fahri (Jurnal Pendidikan Agama Islam, 2025)
The presence of the Independent Curriculum is a strategic response from the government in overcoming learning loss and learning gaps as well as learning gaps that arise due to the pandemic, as well as answering the challenges of education in the Society 5.0 era. Although its implementation has been widely studied at the junior high and high school levels, in-depth studies in the context of Vocational High Schools (SMK), especially for Islamic Religious Education (PAI) and Character Education subjects are still limited. This study aims to analyze the planning, implementation, and evaluation of the Independent Curriculum in the PAI and Character Education subjects at SMK Negeri 1 Kutasari Purbalingga. The method used in this study is a qualitative method with a case study approach. The results of the study show that the school has conducted teacher training and the preparation of teaching materials in stages. However, the implementation of the independent curriculum in the learning process still faces obstacles such as time constraints, teacher workload, and lack of facilities and infrastructure. Learning evaluation is carried out through diagnostic, formative, and summative assessments, but the application of differentiated learning and the principle of freedom to learn is not optimal. This study emphasizes the importance of increasing teacher capacity, strengthening the facilitative role of educators, and more flexible learning management so that the objectives of the Independent Curriculum can be achieved more effectively.